2014
DOI: 10.1186/s12888-014-0277-9
|View full text |Cite
|
Sign up to set email alerts
|

Parental care influences leukocyte telomere length with gender specificity in parents and offsprings

Abstract: BackgroundThere have been several reports suggesting that adverse childhood experiences such as physical maltreatment and long institutionalization influence telomere length. However, there has been no study examining the relationship of telomere length with variations in parental rearing. In the present study, we examined the relationship of leukocyte telomere length with parental rearing in healthy subjects.MethodsThe subjects were 581 unrelated healthy Japanese subjects. Perceived parental rearing was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…We found evidence of telomere shortening in both children with and without a history of institutional care. Consistent with our hypothesis and previous studies of both adults exposed to early caregiving adversity (Beach et al, 2014; Enokido et al, 2014; Kananen et al, 2010; Kiecolt-Glaser et al, 2011), and children exposed to maltreatment, family violence, or high family stress (Drury et al, 2014a, 2012; Gotlib et al, 2014; Shalev et al, 2012), we found exposure to early institutional caregiving resulted in accelerated telomere shortening across middle childhood and adolescence compared to children without any exposure to institutional caregiving.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found evidence of telomere shortening in both children with and without a history of institutional care. Consistent with our hypothesis and previous studies of both adults exposed to early caregiving adversity (Beach et al, 2014; Enokido et al, 2014; Kananen et al, 2010; Kiecolt-Glaser et al, 2011), and children exposed to maltreatment, family violence, or high family stress (Drury et al, 2014a, 2012; Gotlib et al, 2014; Shalev et al, 2012), we found exposure to early institutional caregiving resulted in accelerated telomere shortening across middle childhood and adolescence compared to children without any exposure to institutional caregiving.…”
Section: Discussionsupporting
confidence: 92%
“…Shorter TL has been associated with environmental stress exposure (e.g., neighborhood-level social environmental risk and prenatal tobacco exposure; Theall et al, 2013a, 2013b) and poor caregiving environments for the child (e.g., physical maltreatment, institutional care, poverty; Drury et al, 2012; Mitchell et al, 2014). High quality parental care may buffer the negative impact of adversity on TL (Asok et al, 2013; Enokido et al, 2014). In adults and adolescents, decreased TL has also been associated with cardiovascular disease (Saliques et al, 2010), diabetes (Willeit et al, 2014), and obesity (Müezzinler et al, 2014), all negative health outcomes linked with experiences of early adversity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above benefits for offspring condition and dominance acquisition, infanticide may therefore allow dominant females to improve pup telomere lengths, thus delaying their onset of senescence, extending their dominance tenures and increasing their lifetime reproductive success. While the level and type of parental care has been shown to influence offspring telomere lengths in humans and captive rhesus monkeys (Macaca mulatta) [30,71,72], to our knowledge this is the first evidence that a specific maternal strategy (killing competitor pups) has associated benefits for offspring telomere lengths.…”
Section: Discussionmentioning
confidence: 86%
“…Shalev and colleagues, investigating children, found that there was a relationship between exposure to two or more kinds of violence and shortened telomere length, although numbers in this subgroup were low (n = 39), so definitive conclusions cannot be drawn [9]. Enokido and colleagues [48] showed an association between parenting style and telomere length and also demonstrated a gender-specific response; however, this study involved healthy participants and relied on self-report.…”
Section: Telomere Studiesmentioning
confidence: 92%